Extending the Absorption Limit of BiVO4 Photoanodes with Hydrogen Sulfide Treatment. Issue 7 (28th March 2022) - Gahlawat, Soniya; Schnell, Patrick; Irani, Rowshanak; Ahmet, Ibbi Y.; Choubrac, Leo; Fiechter, Sebastian; Ingole, Pravin P.; Abdi, Fatwa F.
Abstract : Bismuth vanadate is a promising photoanode material for photoelectrochemical water splitting due to its relative stability, low cost, and nontoxic properties. However, its performance is limited by the large bandgap ( E g ) of 2.4 eV, and the record photocurrent is already within 90% of its theoretical limit. Further photocurrent enhancement could only be obtained by increasing its optical absorption, for example, by reducing E g . Herein, sulfur‐incorporated bismuth vanadate (S‐BiVO4 ) thin films are synthesized via spray pyrolysis combined with post‐treatment in hydrogen sulfide environment. Under optimal H2 S treatment conditions, sulfur can be incorporated successfully into the BiVO4 lattice, without the formation of any secondary phases. The use of reactive H2 S, instead of solid sulfur powders, allows us to decrease the required annealing temperature and increase the kinetics for sulfur incorporation into BiVO4 . The E g of the resulting S‐BiVO4 films is decreased by >200 meV (vs. pristine BiVO4 ), which theoretically corresponds to a 20% increase in the theoretical photocurrent limit. Finally, the stability limitation of S‐BiVO4 is overcome by introducing pulsed‐laser‐deposited NiOx protection layers. The modified S‐BiVO4 / NiOx film exhibits higher photocurrent density with no reduction of photocurrent during the 9 h stability test with AM1.5 illumination. Abstract : With demonstrated photocurrents approaching the theoretical limit, the photoelectrochemical (PEC) performance of BiVO4 is limited by the relatively large bandgap. Mild heat treatment under a reactive hydrogen sulfide environment enables sulfur incorporation, which reduces the bandgap and redshifts the photoconductivity onset. The modified films are unfortunately unstable during PEC measurements, but this can be solved by introducing a NiO x protection layer.